2001
DOI: 10.1016/s0304-3959(00)00456-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of P2X3 mRNA expression by peripheral nerve injury in intact and injured neurons in the rat sensory ganglia

Abstract: The P2X(3) receptor is a ligand-gated cation channel activated by the binding of extracellular adenosine 5'-triphosphate (ATP), an agent that has been suggested to have a role in the nociceptive pathway after tissue and nerve injury. After peripheral nerve injury, both down regulation and up regulation of the P2X(3) receptor in sensory ganglion neurons have been observed. The purpose of this study was to examine the precise regulation of P2X(3) mRNA expression in primary sensory neurons after nerve injury. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(95 citation statements)
references
References 44 publications
6
88
0
1
Order By: Relevance
“…Virtually all L4 DRG neurons are spared from axotomy in the L5 SNL model To identify the axotomized sensory neurons in the L4 and L5 DRG after the L5 SNL, we examined the immunoreactivity of ATF3, which has been suggested to be a neuronal injury marker (Tsujino et al, 2000;Tsuzuki et al, 2001). ATF3 immunoreactivity was expressed exclusively in the nuclei of virtually all ipsilateral L5 DRG neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Virtually all L4 DRG neurons are spared from axotomy in the L5 SNL model To identify the axotomized sensory neurons in the L4 and L5 DRG after the L5 SNL, we examined the immunoreactivity of ATF3, which has been suggested to be a neuronal injury marker (Tsujino et al, 2000;Tsuzuki et al, 2001). ATF3 immunoreactivity was expressed exclusively in the nuclei of virtually all ipsilateral L5 DRG neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, after lesions in the peripheral nervous system. P2X3 receptor expression in intact neurons, suggesting a role for this receptor in post-traumatic repair [102]. Following trauma, astrocytes increased expression of P2X4 receptors thereby inducing trombospondin-1 secretion, which constitutes an extracellular molecule for synapse formation contributing to CNS remodeling [81,103].…”
Section: Epilepsymentioning
confidence: 99%
“…The up-regulation of ATF3 in DRG neurons was first noted at day 1 following the initial intravenous infusion and this increased expression was still present at day 10 post-infusion (the latest time point examined). Previous studies have shown that ATF3 is induced by stress stimuli and cellular damage and may have a survival/ regenerative function in sensory neurons (Seijffers et al, 2006) Following axotomy of sensory nerve fibers within the sciatic nerve (Tsujino et al, 2000), spinal nerves (Wang et al, 2003), or distal branches of the sciatic nerve (Tsuzuki et al, 2001) in the rat, ATF3 is up-regulated in neuronal cell bodies within 24 hours and this de novo expression can be maintained for weeks (Tsujino et al, 2000;Tsuzuki et al, 2001;Shortland et al, 2006). Upregulation of ATF3 in the DRG of axotomized nerves is prevented by the exogenous administration of nerve growth factor (Averill et al, 2004) and glial cell derived nerve growth factor (Wang et al, 2003).…”
Section: Impact Of Intravenous Paclitaxel On Sensory Neurons In the Drgmentioning
confidence: 99%